Corporatization Strategies of Philippine State Universities and Colleges Under Republic Act 8292: A Systematic Literature Review - Melissa S. Carbonell (Universal Journal of Educational Research)
Universities and Colleges (SUCs) through its creation, aiming to address budget deficits while establishing independent financial structures and management systems. This systematic literature review examines the nature of corporatization in Philippine State Universities and Colleges (SUCs) in terms of governance, financial performance, educational quality, and its implications. This review follows the PRISMA and involves 32 sources from Google Scholar, ProQuest, Philippine E-Journals, and ERIC. Some of the implications revealed are that corporatization has led to increased sources of revenue generation, enhanced financial performance, and reduced reliance on subsidies. However, issues such as fluctuating profitability, operational inefficiency, and concerns about access to education and its quality persist. Modern IGPs can harness their potential for sustainability through robust governance systems, effective financial management, and strategic planning, which in turn support regional development. However, balancing economic and educational goals proves challenging. Several recommendations are made to strengthen financing and financial management, corporate governance, and quality assurance procedures, ensuring that the pursuit of corporatization does not erode educational ideals. Further research is needed to determine whether and to what extent corporatization is a sustainable model in terms of financial performance, academic quality, and affordability. Analyzing social effects and technological changes in governance operations, in conjunction with business functions, enables a crucial understanding of how educational institutions approach management and formulate their policies.